Significance of Branding in Industrial Marketing - Raizada, Sumesh (Indian Journal of Marketing, 2012)
Branding is primarily done to create personality of a product and to differentiate it from other similar offerings of the competitors. A brand not only identifies a product from among the commodities but also conveys the image, goodwill and excellence of the marketing organization. Though most of the FMCG, insurance, automobile or pharmaceutical firms separately brand their offerings, those dealing in industrial products relatively attach less importance to this vital concept of marketing. The industrial product manufacturers, which are often small and medium enterprises, usually consider branding as expensive and irrelevant for their businesses. However, with the spread of globalization, where sourcing and manufacturing activities are carried out across the world, immense opportunities now exist for the original equipment manufacturers (OEM) to market their products globally. Industrial product marketers, whether large or small, therefore, need to formulate their branding strategies effectively in order to compete with the global competitors. The present paper shall briefly discuss the process generally followed in the business marketing and will explore the issues involved in the branding of industrial products. It shall also investigate the branding strategies of few B2B firms in India and abroad. The paper shall finally conclude by proposing the strategies and a model for industrial product branding in the contemporary business environment. The paper is based upon secondary information sources from print as well as the electronic medium.